RP-HPLC Method for Simultaneous Estimation of Cefepime Hydrochloride and Tazobactam Sodium in Bulk and Pharmaceuticals - Sagar R. Tamboli; Dipak D. Patil (Journal of Chemistry)
A precise, accurate, sensitive and robust RP-HPLC method was developed for cefepime hydrochloride and tazobactam sodium in bulk and pharmaceutical formulation. Chromatographic separation was achieved on PrincetonSPHER-100 C-18 column (250 mm × 4.6 mm i.d., 5 µm) at ambient temperature. A binary mobile phase consisting of 25 mM potassium dihydrogen phosphate buffer, pH 6.2 and acetonitrile (94 : 6, v/v) was delivered through a column at a flow rate of 1 mL/min. Measurement was performed at a wavelength 210 nm. The method was linear over the concentration range of 4–24 µg/mL () for cefepime and 0.5–3.0 µg/mL () for tazobactam. The percentage content found for cefepime was 101.12 ± 0.49 and for tazobactam was 101.33 ± 1.17 in the pharmaceutical formulation. The method was validated for linearity, precision, accuracy, sensitivity and robustness as per ICH Q2 (R1) guideline.